The oldest guard forging the Zionist settler past - Halperin, Liora R. (Stanford Stanford University Press, 2021)
Introduction : mother of the colonies -- Private farmers and the origins of "First Aliyah" claims-making -- Arab labor and the rhetoric of hierarchical coexistence in Mandate Palestine -- The old guard on display -- The colony and the village : constructions of coexistence after the Nakba -- Jewish immigrants and the politics of settler "First Ones," 1948-1967 -- Conclusion : thinking about the First Aliyah after 1967.
"The Oldest Guard tells the story of Zionist settler memory in and around the private Jewish agricultural colonies (moshavot) established in late nineteenth-century Ottoman Palestine. Though they grew into the backbone of lucrative citrus and wine industries of mandate Palestine and Israel, absorbed tens of thousands of Jewish immigrants, and became known as the "first wave" (First Aliyah) of Zionist settlement, these communities have been regarded-and disregarded-in the history of Zionism as sites of conservatism, lack of ideology, and resistance to Zionist Labor politics. Treating the "First Aliyah" as a symbol created and deployed only in retrospect, Liora Halperin offers a richly textured portrait of commemorative practices between the 1920s and the 1960s. Drawing connections to memory practices in other settler societies, she demonstrates how private agriculturalists and their advocates on the Zionist center and right celebrated and forged the "First Aliyah" past as a model of private ownership, political impartiality, and hierarchical relations with hired rural Palestinian labor. The Oldest Guard reveals the centrality of settlement to Zionist collective memory and the politics and erasures of Zionist settler "firstness.""--
Includes bibliographical references and index
Keywords: Zionism -- Palestine -- Historiography; Jews -- Colonization -- Palestine -- History; Agricultural colonies -- Palestine -- History; Collective Memory -- Palestine -- History; Collective Memory -- Israel -- History; Palestine -- History -- 1917-1948; Israel -- History -- 1948-1967